Time-Frequency Analysis and Hermite Projection Method Applied to Swallowing Accelerometry Signals. (3rd May 2010) - Orović Orović, Irena Irena; Stanković Stanković, Srdjan Srdjan; Chau Chau, Tom Tom; Steele Steele, Catriona M. Catriona M.; Sejdić Sejdić, Ervin Ervin
Abstract : Fast Hermite projections have been often used in image-processing procedures such as image database retrieval, projection filtering, and texture analysis. In this paper, we propose an innovative approach for the analysis of one-dimensional biomedical signals that combines the Hermite projection method with time-frequency analysis. In particular, we propose a two-step approach to characterize vibrations of various origins in swallowing accelerometry signals. First, by using time-frequency analysis we obtain the energy distribution of signal frequency content in time. Second, by using fast Hermite projections we characterize whether the analyzed time-frequency regions are associated with swallowing or other phenomena (vocalization, noise, bursts, etc.). The numerical analysis of the proposed scheme clearly shows that by using a few Hermite functions, vibrations of various origins are distinguishable. These results will be the basis for further analysis of swallowing accelerometry to detect swallowing difficulties.